First determination of the spin-parity of ${Ξ}_{c}(3055)^{+,0}$ baryons - Aaij, Roel; Abdelmotteleb, Ahmed Sameh Wagih; Abellan Beteta, Carlos; Abudinén, Fernando Jesus; Ackernley, Thomas; Adefisoye, Ayomide Matthew; Adeva, Bernardo; Adinolfi, Marco; Adlarson, Patrik Harri; Agapopoulou, Christina; Aidala, Christine Angela; Ajaltouni, Ziad; et al. (Physical review letters, 2025)
The ${Ξ_{b}^{0(-)}→Ξ_{c}(3055)^{+(0)}(→ D^{+(0)}{Λ})π^{-}}$ decay chains are observed, and the spin-parity of ${Ξ}_{c}(3055)^{+(0)}$ baryons is determined for the first time. The measurement is performed using proton-proton collision data at a center-of-mass energy of $\sqrt{s}=13\,\text{TeV}$, corresponding to an integrated luminosity of $5.4\,\text{fb}^{-1}$, recorded by the~$\text{LHCb}$ experiment between 2016 and 2018. The spin-parity of the ${Ξ}_{c}(3055)^{+(0)}$ baryons is determined to be $3/2^{+}$ with a significance of more than $6.5σ$ ($3.5σ$) compared to all other tested hypotheses. The up-down asymmetries of the ${Ξ_{b}^{0(-)}→Ξ_{c}(3055)^{+(0)}{π}^{-}}$ transitions are measured to be $-0.92±0.10±0.05$ ($-0.92±0.16±0.22$), consistent with maximal parity violation, where the first uncertainty is statistical and the second is systematic. These results support the hypothesis that the ${Ξ}_{c}(3055)^{+(0)}$ baryons correspond to the first $D$-wave $λ$-mode excitation of the ${Ξ}_{c}$ flavor triplet.